Multi‐Model Assessment of Groundwater Recharge Across Europe Under Warming Climate - Rohini Kumar; Luis Samaniego; Stephan Thober; Oldrich Rakovec; Andreas Marx; Niko Wanders; Ming Pan; Falk Hesse; Sabine Attinger (Earth's Future)
Abstract Climate change threatens the sustainable use of groundwater resources worldwide by affecting future recharge rates. However, assessments of global warming's impact on groundwater recharge at local scales are lacking. This study provides a continental‐scale assessment of groundwater recharge changes in Europe, past, present, and future, at a (5×5) km2 resolution under different global warming levels (1.5, 2.0, and 3.0 K). Utilizing multi‐model ensemble simulations from four hydrologic and land‐surface models (HMs), our analysis incorporates E‐OBS observational forcing data (1970–2015) and five bias‐corrected and downscale climate model (GCMs) data sets covering the near‐past to future climate conditions (1970–2100). Results reveal a north‐south polarization in projected groundwater recharge change: declines over 25%–50% in the Mediterranean and increases over 25% in North Scandinavia at high warming levels (2.0–3.0 K). Central Europe shows minimal changes (±5%) with larger uncertainty at lower warming levels. The southeastern Balkan and Mediterranean region exhibited high sensitivity to warming, with changes nearly doubling between 1.5 and 3.0 K. We identify greater uncertainty from differences among GCMs, though significant uncertainties due to HMs exist in regions like the Mediterranean, Nordic, and Balkan areas. The findings highlight the importance of using multi‐model ensembles to assess future groundwater recharge changes in Europe and emphasize the need to mitigate impacts in higher warming scenarios.